HbA1c for type 2 diabetes diagnosis in Africans and African Americans: Personalized medicine NOW! - Andrew D Paterson (PLoS Medicine)
Andrew Paterson discusses findings from a new study that shows HbA1c screening for diabetes will leave 2% of African Americans undiagnosed and how personalised medicine is needed.